Aflatoxins contamination in Pakistani brown rice: a comparison of TLC, HPLC, LC–MS/MS and ELISA techniques. (December 2014) - Iqbal, Javed; Asghar, Muhammad Asif; Ahmed, Aftab; Khan, Mobeen Ahmed; Jamil, Khalid
Abstract Advancement in the field of analytical food-chemistry has explored various experimental techniques for aflatoxins (AFs) quantification. The present study was aimed to compare four different techniques; thin-layer chromatography (TLC), high-performance liquid chromatography (HPLC), liquid chromatography–tandem mass spectrometry (LC–MS/MS) and enzyme-linked immunosorbent assay (ELISA) for the analysis of aflatoxin B1 (AFB1), B2 (AFB2), G1 (AFG1) and G2 (AFG2) in brown rice (n = 120) being collected from Karachi, Pakistan. All the four assays provide precised, accurate and comparable results. However, some differences were observed. For instance, TLC, HPLC and LC–MS/MS methodologies offered the advantage of the quantification of individual toxins in contrast to ELISA technique. The contamination ranges of AFB1/AFB2 as determined by TLC, HPLC and LC–MS/MS were 1.18–9.97/0.59–1.52, 0.16–10.54/0.26–1.35 and 0.11–10.88/0.38–1.48 µg/kg, respectively. However, AFG1 and AFG2 were not detected in any tested samples. Furthermore, owing to low-detection limit and sensitivity, HPLC and LC–MS/MS methodologies have identified greater number of contaminated samples in comparison to TLC and ELISA techniques. The overall average results of total AFs as provided by HPLC (3.79 µg/kg) and LC–MS/MS (3.89 µg/kg) were found higher in comparison to TLC (3.68 µg/kg) and ELISA (3.70 µg/kg). On the basis of achieved results, it was concluded that TLC, HPLC, LC–MS/MS and ELISA techniques are valuable tool for the quantification of AFs in cereals and grains. Furthermore, HPLC and LC–MS/MS techniques offer an added advantage for the detection of AFs in diminutive levels.